Voicing the Differend: A Study of Contested Histories and Disputed Territories in Shashi Tharoor’s Riot - Sadiq, Rashid Masood (Annals of Human and Social Sciences, 2023)
This research paper studies the fictionalized articulations of causes of antagonistic relations between the Hindus and the Muslims of India in Shashi Tharoor’s Riot, a Novel (2001). The novel evinces a desire for peaceful syncretic and multicultural cohabitation of these two communities, a vision enshrined in Jawaharlal Nehru’s idea of ‘Unity in Diversity’. The longing, however, is thwarted because of the contentious claims of the Hindus and Muslims of India over Indian history and territory. The irresolvability of these contentions can be understood through Jean Francois Lyotard’s idea of differend which he defines as “a case of conflict between (at least) two parties that cannot be equitably resolved for lack of a rule of judgment applicable to both arguments”. By unpacking the differend between two parties, Hindutva and the Muslims, the novel highlights the status of the Muslims of India as a threatened minority and the discrimination faced by them in multiple forms. It, however, exhibits a confidence in the ability of secular nature of Indian constitution, its resilient democracy, and absorptive syncretic Indian tradition to overcome the sense of wrong and injustice felt by the Muslims.